Flavius Josephus : translation and commentary / edited by Steve Mason. - Josephus, Flavius (Brill, 2000)
Flavius Josephus, the first-century Jewish historian, is without a doubt the most important witness to ancient Judaism from the close of the biblical period to the aftermath of the destruction of the temple in 70 CE. After fighting against the Romans in the war of 66-73 and surrendering in the earliest phase of the campaign, he moved to Rome where he began a productive literary career. His four surviving works - Judean War, Judean Antiquities, Life, and Against Apion, in thirty Greek volumes - provide the narrative structure for interpreting the other, more fragmentary written sources and physical remains for this period. His descriptions of the Temple, the Judean countryside, Jewish-Roman relations and conflicts, and groups and institutions of ancient Judea have become indispensable for the student of early Judaism, of Classics, and of Christian origins alike. This project aims to assist every serious reader of Josephus by providing a new literal translation, along with a commentary suggesting literary and historical connections. This is the first comprehensive literary-historical commentary on the works of Flavius Josephus in English.